Evaluación de la viabilidad técnico financiera de la implementación de la tecnología de perforación direccional con revestimiento en la sección intermedia 12 ¼” de un pozo en el Campo Chichimene (2016)
This document evaluates the technical and financial viability of implementing the Directional Casing while drilling technology in 12 ¼’" section (intermediate section) of wells located in the Chichimene Field. First, the geological characteristics of the field and the generalities of the Directional Casing while drilling technology are described. The technical assessment initially involves the identification of the main operational problems that have arisen frequently as a result of the drilling of the intermediate section of wells in the Chichimene Field and based on this, model the main components of a well design.